2004
DOI: 10.1007/s10238-004-0030-7
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen levels in hypercholesterolemic smokers and non-smokers in relation to age and gender

Abstract: Elevated total cholesterol and plasma fibrinogen levels and smoking are risk factors for cardiovascular disease, whose inter-relationships are influenced by both gender and age. The aim of this study was to investigate the effect of smoking on fibrinogen levels in a hypercholesterolemic population subdivided on the basis of gender and age. The study included 492 hypercholesterolemic subjects, divided into four subpopulations: men and women, aged 26-49 and 50-66 years. Mean fibrinogen levels among smokers and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…Serum fibrinogen concentrations increase parallel to age which is the main determinant [11,12]. Smoking on the other hand, is the second most important factor associated with fibrinogen [12,13], with more marked alterations in women [13]. Possible explanations for this are related to the inflammatory reaction, endothelial injury, reduced fibrinolysis and platelet activity induced by smoking [14].…”
Section: Discussionmentioning
confidence: 99%
“…Serum fibrinogen concentrations increase parallel to age which is the main determinant [11,12]. Smoking on the other hand, is the second most important factor associated with fibrinogen [12,13], with more marked alterations in women [13]. Possible explanations for this are related to the inflammatory reaction, endothelial injury, reduced fibrinolysis and platelet activity induced by smoking [14].…”
Section: Discussionmentioning
confidence: 99%
“…Smoking on the other hand, is the second most important factor associated with fibrinogen [12,13], with more marked alterations in women [13]. Possible explanations for this are related to the inflammatory reaction, endothelial injury, reduced fibrinolysis and platelet activity induced by smoking [14].…”
Section: Discussionmentioning
confidence: 99%
“…Smoking and hypercholesterolemia lead to endothelial dysfunction, which is an early stage of atherogenesis (Witztum and Steinberg, 1991) Smoking elevates plasma fibrinogen levels among hypercholesterolemic men and women (Schuitemaker et al, 2004). Recent data showed that the coexistence of smoking and hypercholesterolemia increase serum levels of inflammatory markers (US Department of Health and Human Services, 1997).…”
Section: Introductionmentioning
confidence: 99%